Axial compressive testing of concrete-filled steel tubular members incorporating demolished concrete lumps - Hay, James (2025)
Compound concrete (CC) can be cast by mixing fresh concrete (FC) with coarsely crushed demolished concrete lumps (DCLs) that have been obtained from a demolished structure. DCLs are larger than recycled concrete aggregates and are treated as a whole concrete replacement instead of a coarse aggregate replacement. This distinction implies that CC uses less Portland cement in comparison to FC, which reduces the embodied carbon of this material. A significant challenge for the broader application of CC is the lower compressive strength and ductility stemming from the weak interface between the DCLs and surrounding FC. However, the use of CC in concrete-filled steel tubes (CFSTs) and concrete-filled stainless-steel tubes (CFSSTs) has the potential to mitigate this issue due to the lateral confinement provided by the steel tube. Furthermore, the use of CFSST members is particularly favourable in corrosive conditions such as marine environments due to the material properties of stainless-steel.